Simulation on Force Tracking Control of a Magnetorheological Damper under Impact Loading - Pokaad, Alif Zulfakar; SAID, MD RADZAI; Ahmad, Fauzi; Kamaruddin, Mohd Nazeri (Trans Tech Publications, Switzerland, 2014)
This paper focuses on the design of the control structure which consists of inner loop controller employed for MR damper under impact loading by using computer simulation. The simulation is done by using MATLAB 7.0. The structure of the inner loop control for the proposed MR damper model uses a simple PI control to achieve the desired force. In this simulation, the MR damper model that has been validated with the experimental result is used to simulate the actual force that produced by MR damper. The performance of inner loop controller to track the actual force produced by MR damper by obtaining the several input functions which are half wave of sinusoidal, saw-tooth, square and random functions of desired force with the variation in pendulum mass of 15 kg and 20 kg are investigated. It can be seen clearly that under several input functions, the proposed polynomial model with PI controller has the good ability to track the desired damping force under impact loading.